Does mental wellbeing mediate the relationship between perceived stress and perceived health? - Teh, Hui Chian. (2012)
With increasing awareness and attention on mental wellbeing from both health policymakers and researchers, there is a need to understand its role in health. This study evaluated the relationship between perceived stress and perceived health in young participants and examined a potential underlying mechanism by testing mental wellbeing as a mediator. 200 undergraduates aged 21to 26 in Singapore completed the questionnaires: Perceived Stress Scale (PSS-10), Health Status Questionnaire (HSQ-12) and Asian Mental Wellbeing scale (AMWB) which assess perceived stress, perceived health and mental wellbeing respectively. Validation of the English PSS-10 for the Singapore population was carried out. Confirmatory factor analysis excluded an insignificant item, item 7, and resulted in two factors, namely Perceived Distress and Perceived Coping. Of interest, the Singapore sample reported greater perceived stress compared to that reported from other studies. Findings from linear multiple regressions indicated that perceived stress was significantly negatively associated with perceived health. In addition, Sobel test and bootstrapping results showed that mental wellbeing partially mediated the relationship between perceived stress and perceived health; although it is acknowledged that this association could be bidirectional. Findings from the present study suggest that future research could focus on reducing stress and improving mental wellbeing to alleviate the effect of stress on health. Implications for policymakers in terms of health promotion are discussed.